Examining the Employer-Size Wage Premium in the Manufacturing, Retail Trade, and Service Industries Using Employer–Employee Matched Data - Bayard, Kimberly; Troske, Kenneth R (American Economic Review, 1999)
Examining the Employer-Size Wage Premium in the Manufacturing, Retail Trade, and Service Industries Using Employer-Employee Matched Data by Kimberly Bayard and Kenneth R. Troske. Published in volume 89, issue 2, pages 99-103 of American Economic Review, May 1999